THEORY OF DEMOGRAPHIC RESEARCH IN THE UNIVERSITY SCIENTIFIC SCHOOL - N. V. Zvereva (Статистика и экономика)
The scientific article is targeted at researchers of social processes in society attributable to the group of social anomalies. In particular, we are talking about one of the most painful issues: the influence of alcohol to the whole society. The impact that begins to destroy the society at the level of its primary cell – families, and which will bring the turn to the finish – the complete, manifested in the degradation of the whole society. The object of the study indicated market of alcoholic beverages, i.e. an economic category, not a medical artifact, as is customary in the vast majority of articles devoted to the problem of such a devastating impact. A statistical study is conducted regarding the quantitative assessment of the labeled dependency: opening patterns, trend analysis, modeling, socio-economic process that determines the level of alcohol in crime. In addition, the issue of the influence of key social factors indicated the relationship of the market of strong drinks and its social consequences is covered. We are talking about the vector of development of the society: at the creation, or survival in the current socio-economic conditions, or even at full degradation. The conditions that each particular person is promised to "balance the books" or to develop. In the first case, and that we are watching from the times of socialist stagnation, "balance" is the products purchased in the alcohol market. Further, impact on society, and as a result, the newly increased demand in the alcohol market. There are obvious implications for the collective cash fund of the state budget, which task is to fund extensive programs to prevent alcoholic crime and preventive measures of a medical nature, help the citizens, and put themselves and society as a dependence on "solution – crafty". In the course of scientific research, extensive information and methodological base is involved. In the first case, statistical data of bodies of state statistics and departmental statistics of the internal affairs bodies. The methodological framework is presented in the traditional tools of statistics science and practice in determining the complexity of almost any ongoing statistical research. These are the methods of correlation and regression, statistical modelling of the relationship between the time series of analytical alignment of the time series and constructing short-term forecasts. Such a set of statistical indicators for the quantitative assessment of patterns and trends, modelling of interrelations of indicators of the market of alcoholic beverages, the level of living of the population and alcohol crime is first considered.